MUSLIM MORALITY AS FOUNDATION FOR SOCIAL HARMONY - Bensaid, Benaouda; Machouche, Salah (Journal of Al-Tamaddun, 2019)
The argument inherent in this study is that the Islamic framework on social coexistence and harmony stipulates moral capital as a bridge for community’s inter-connectivity, interaction, and development, and that, for Muslims, morals act as an effective catalyst for constructing social coexistence and harmony. This study discusses the concept of Islamic social ethics and moral development in the context of society, followed by an inquiry into the ways and means according to which Muslim ethics may contribute and sustain social rapprochement, mutual support and social justice. The study aims to identify the prevalent framework for Muslim social morality, which can be of benefit to effective social policy, increasing civic engagement, developing an inclusive universal moral education, or furthering multicultural tolerance. Using textual approach, this study shows how Islam capitalizes on individual and collective morality towards the effective engineering of sustainable communities’ relations and development. Further empirical studies on the contribution of Muslim morals in lieu of fortifying community development and social harmony would contribute to the way of elucidating the Muslim projection of theoretical moral ideals in real life conditions as well as tracing the convergences and divergences between Muslim theory and practices with regards to the application of morals to personal and communal settings, and more importantly in our context the shaping of communities’ rapprochement, co-existence and harmony.